2008
DOI: 10.1309/w01y0b808emeh12l
|View full text |Cite
|
Sign up to set email alerts
|

CSF Multianalyte Profile Distinguishes Alzheimer and Parkinson Diseases

Abstract: The therapeutic imperative for Alzheimer disease (AD) and Parkinson disease (PD) calls for discovery and validation of biomarkers. Increased cerebrospinal fluid (CSF) tau and decreased amyloid (A) beta42 have been validated as biomarkers of AD. In contrast, there is no validated CSF biomarker for PD. We validated our proteomics-discovered multianalyte profile (MAP) in CSF from 95 control subjects, 48 patients with probable AD, and 40 patients with probable PD. An optimal 8-member MAP agreed with expert diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
194
3
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(212 citation statements)
references
References 17 publications
10
194
3
5
Order By: Relevance
“…As many Ab-binding proteins, such as TTR, apoE, apoJ, and apoA1, are known to accumulate with Ab in amyloid No Ab bands were detected in the littermate mice; n ¼ 4 each cases deposits 5,17 and the level of DBP in CSF is increased in AD patients, 11,15,16 we examined whether DBP is present in the amyloid plaques of brains from AD patients and transgenic animal model of AD. We double-stained human AD and control brain with antibodies against Ab (4G8) and DBP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As many Ab-binding proteins, such as TTR, apoE, apoJ, and apoA1, are known to accumulate with Ab in amyloid No Ab bands were detected in the littermate mice; n ¼ 4 each cases deposits 5,17 and the level of DBP in CSF is increased in AD patients, 11,15,16 we examined whether DBP is present in the amyloid plaques of brains from AD patients and transgenic animal model of AD. We double-stained human AD and control brain with antibodies against Ab (4G8) and DBP.…”
Section: Resultsmentioning
confidence: 99%
“…Although the level of DBP in CSF has been known to be increased in AD patients, and several lines of evidence have suggested that DBP plays a role in AD, 11,15,16,32 there is no direct evidence of whether or how DBP affects AD-related pathology. Our data clearly show that DBP interacts directly with Ab and reduces the formation of aggregated Ab.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using CSF of PD patients, Zhang et al 80 reported on the first large scale proteomic experiment, the presence of novel BMs for PD and AD. Of these BMs, however, only A␤ and tau proteins displayed different levels among controls, AD and PD, and between AD and PD as expected.…”
Section: Fig 2 Pre-diagnostic Phase Of Parkinson's Disease (Pd)mentioning
confidence: 99%